Business process change and inadvertent mischarging. (1st December 2008) - Brady, Malcolm; Lynn, Theodore; Davis, Paul
This paper examines a situation whereby a process change in one division of an organisation, through a cause and effect chain, resulted in the organisation overbilling a customer. The paper examines the mechanism by which the overbilling occurred and discusses the organisation's response when overbilling was brought to its attention. The paper uses an in-depth case study approach and is written in the form of an investigative report. The paper demonstrates clearly that due to the complexity of the modern organisation over-billing can occur unbeknownst to a company. The paper also shows that the boundary-spanning processes of the organisation failed: the customer service process failed to deal with the over-billing situation. The paper concludes that misbilling was not intentional but was the result of an innovation in one business process (meter reading) whose consequence for another business process (billing) was not fully understood or explored.